REVITALISASI DETERMINASI DIRI PADA MAHASISWA PENDIDIKAN AGAMA ISLAM FAKULTAS ILMU AGAMA ISLAM UNIVERSITAS ISLAM INDONESIA - Sholehah, Umi (Universitas Muhammadiyah Jember, 2020)
Learning is a process done for getting new knowledge and implementing it in everyday. Learning must be bendable according to one?s talent, interest, and abilities. In contrast to what happens to some students in a Islamic religious education study program that has studied in uninterested majors. The goal of this research is : to understand how to turn back the determination of a student after having been inhibitions in the learning process; and to know the supporting and retardation factors. The kind of research used in this study is qualitative and use a psychological approach of education. The techniques used in this research are purposive and snowball sampling. As well as data-collection techniques using methods of observation, interviews, and documentation. This study showed that students who study in uninterested majors have a way of revitalizing their own determination by increasing autonomy, competence, and related. The 2015 student of Islamic Education, has boosted its self-determination by submitting to the university?s internal and external activities program. Also, the pattern of communication with other students and teachers is established. As far as supporting factors are concerned, students have the freedom to express themselves and engage in college activities. The limiting factor is the overself-esteem of a dominant student and the challenge facing any student who feels it is a reflection of a college degree in entitlement.